Challenges of Transition from Joint Aviation Authorities 1 Federal Aviation Administration ... - Galović, Borivoj; Novoselić, Goran; Čurepić, Danko (Promet - Traffic&Transportation, 2003)
The work presents certain challenges that occur in the processof preparation and gradual transition to the unique Europeanagency I service of air traffic safety, as well as the interactionof EASA with other similar services I agencies in the world.The new agency, in the new legal and functional environmentthat is being created, has to take over painlessly and withoutany break, the important functions and responsibilities of theJAA/FAA related to air traffic safety and airworthiness at theEuropean and world level.